The Costs of Job Loss and Task Usage - Antti Kauhanen; Krista Riukula (The Research Institute of the Finnish Economy (ETLA), 2019)
This study examines the degree to which the effects of job loss depend on task usage and task distance to other jobs. We use linked employer-employee data and representative survey data on task usage and plant closures to identify individuals who have lost their jobs involuntarily. We find that the heterogeneity in the cost of job loss is linked to task usage. Workers in origin jobs with high levels of social tasks have smaller employment and earnings losses, whereas workers in routine jobs face larger wage losses. Instead, the distance in task usage between the origin job and other jobs does not matter when the usage of manual, abstract, routine and social tasks is taken into account.
Keywords: J62; J65; J31; J24; 330; Job loss; Wage loss; Linked Employer-Employee Data; Specific Human Capital